Experimental Study on the Sediment-Trapping Performance of Different Coastal Protection Structures in a High-Tidal Range Area - Hao-Nan Hung; Hsin-Hung Chen; Ray-Yeng Yang (Journal of Marine Science and Engineering)
This study evaluates the sediment-trapping performance of three coastal protection structures—submerged breakwaters, derosion lattices, and a composite seawall–submerged breakwater system—under monsoon and typhoon wave conditions. Physical model experiments were conducted in a wave basin with a movable-bed setup and variable water levels to simulate high tidal range environments. The results show that all three structures significantly improved sediment retention in the landward region, with the composite system performing best, followed by the submerged breakwaters and derosion lattices. However, in the seaward region, the sediment retention was 55.36% lower with submerged breakwaters and 126.79% lower with the composite system, relative to the no-structure case under monsoon wave conditions. Notably, the derosion lattice was the only structure that consistently achieved greater sediment retention than the no-structure case on both the seaward and landward sides.